Sistem Penyiraman Otomatis berbasis Arduino Pada Kebun Tomat Menggunakan Sensor Soil Moisture - Dimas Rizky Putra Pratama; Nunu Nugraha Pratama; Muhamad Riyad Ariwibowo (The Indonesian Journal of Computer Science, 2024)
Soil is a plant growing medium that contains soil minerals that can affect the condition of the soil, including soil temperature and moisture. Good soil conditions have moisture values above 50% - 80%. In addition to soil moisture, other factors that affect plant growth, one of which is temperature, the ideal soil temperature for some types of plants is in the range of 20ºC to 35ºC, tomato plants can grow well with a minimum of soil moisture condition above 50%, therefore, testing is needed to determine the condition of the soil, by making an Arduino – based Automatic Watering System Using Soil Moisture Sensor. The test results on the soil moisture sensor show that ideal soil conditions exist at night, with the average of each sensor used is 66,92%, 60,19%, 61,81%, 66,86%. Thus, pH sensors testing obtained an average error value of 3,89%, and a water flow sensor test value with an average value of 7,828 L/min.